Development of an effective risk reduction system at food industry enterprises - I. P. Mitrofanova; D. A. Rizak; V. A. Bagin (Вестник университета)
The current work is relevant due to the existence of problems in the food industry that are directly related to hazards presented at the earliest stages in the production. For the consumer, to maintain his physical health when eating is of great importance, and for the manufacturer, this is a matter of economic well-being through the production and supply of safe products for consumption. The purpose of the study was to develop suggestions focused on the use of an extended risk-based approach in the format of a food safety management system. If а systematic analysis of the most significant risk-based technologies is applied, it will allow to build a workable and effective protection system and minimise losses from impact of dangerous factors on an organisation’s processes. The authors studied the most interesting international and domestic standards that address the problem of reducing risks and hazards for food industry enterprises, and chose the most effective methods that complement each other. A logically built four-stage model of risk treatment at the operational and organisational levels of the enterprise and recommendations for expanding the risk-based approach in the food safety management system are the results of the work.